2022
DOI: 10.3389/fpls.2022.916231
|View full text |Cite
|
Sign up to set email alerts
|

Rose Rosette Disease Resistance Loci Detected in Two Interconnected Tetraploid Garden Rose Populations

Abstract: Rose rosette disease (RRD), caused by the Rose rosette emaravirus (RRV), is a major threat to the garden rose industry in the United States. There has been limited work on the genetics of host plant resistance to RRV. Two interconnected tetraploid garden rose F1 biparental mapping populations were created to develop high-quality tetraploid rose linkage maps that allowed the discovery of RRD resistance quantitative trait loci (QTLs) on linkage groups (LGs) 5, 6, and 7. These QTLs individually accounted for arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…Here, we report that Rosa wichurana thornless ARE showed few symptoms, whereas R. wichurana poterifolia ARE and R. soulieana RM showed moderate to severe symptoms. In addition, the source of the RRD resistance on LG5 appears to be derived from Rosa wichurana ‘Basye’s Thornless’ [ 28 , 29 ]. It is important to note that RRD resistance in one accession does not mean all accessions within the species are resistant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we report that Rosa wichurana thornless ARE showed few symptoms, whereas R. wichurana poterifolia ARE and R. soulieana RM showed moderate to severe symptoms. In addition, the source of the RRD resistance on LG5 appears to be derived from Rosa wichurana ‘Basye’s Thornless’ [ 28 , 29 ]. It is important to note that RRD resistance in one accession does not mean all accessions within the species are resistant.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been reported that the QTL for partial resistance on LG5 affects both symptom development as well as virus titer as measured by Ct values [ 28 , 29 ]. This implies that this resistance QTL affects virus proliferation in the host plant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their growth and flower quality is often damaged by various diseases, including black spot, powdery mildew, and gray mold. However, only a small number of disease resistance genes have been cloned and studied [ 24 , 25 , 47 , 62 ]. In recent years, the publication of the reference genome and related omics data pertaining to Rosa plants has provided a shortcut for the identification of disease resistance genes [ 23 , 36 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polyploids, organisms containing more than two sets of chromosomes, play a dominant role in many sectors of agriculture [Udall and Wendel, 2006]. Consequently, numerous breeding programs are dedicated to the agricultural improvement of polyploids [Ferrão et al, 2018, Shirasawa et al, 2017, Amadeu et al, 2021, Lau et al, 2022]. In these programs, breeders frequently generate “F1 populations” of full siblings for various tasks, such as QTL mapping [Amadeu et al, 2021], linkage mapping [Bourke et al, 2018, Mollinari and Garcia, 2019], and genomic selection [Ferrão et al, 2021], all of which are crucial for crop improvement.…”
Section: Introductionmentioning
confidence: 99%